2009
DOI: 10.3109/09687680903321081
|View full text |Cite
|
Sign up to set email alerts
|

Movement of the S4 segment in the hERG potassium channel during membrane depolarization

Abstract: The hERG potassium channel is a member of the voltage gated potassium (Kv) channel family, comprising a pore domain and four voltage sensing domains (VSDs). Like other Kv channels, the VSD senses changes in membrane voltage and transmits the signal to gates located in the pore domain; the gates open at positive potentials (activation) and close at negative potentials, thereby controlling the ion flux. hERG, however, differs from other Kv channels in that it is activated slowly but inactivated rapidly - a prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
8
16
0
Order By: Relevance
“…Together, these data suggest that the fast initial fluorescence quenching from the labelled E519C:C445V:C449V channel may provide an accurate report of a rapid environmental change at the top end of S4 in hERG channels that signals channel activation. These results are consistent with recent work using the thiol modifying reagent pCMBS which showed that the extent of exposure of S4 in hERG during depolarization is similar to other Kv channels and KvAP [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Together, these data suggest that the fast initial fluorescence quenching from the labelled E519C:C445V:C449V channel may provide an accurate report of a rapid environmental change at the top end of S4 in hERG channels that signals channel activation. These results are consistent with recent work using the thiol modifying reagent pCMBS which showed that the extent of exposure of S4 in hERG during depolarization is similar to other Kv channels and KvAP [32].…”
Section: Discussionsupporting
confidence: 92%
“…Fluorescence quenching accords with TMRM movement to a more hydrophilic environment, and thus the fast fluorescence quenching we have described from E519C labelling (Figs. 5– 7) may be tracking voltage sensor movement outward, as was suggested in other studies using MTSET accessibility [31] or pCMBS [32]. In Shaker A359C, and in Kv1.5 channels at A379C, voltage-dependent fluorescence quenching is predominantly fast and monotonic upon depolarization and the F-V relationship overlays [17] or approximates [12] the Q-V relationship, which is approximately 20 mV hyperpolarized with respect to the G-V relationship.…”
Section: Discussionmentioning
confidence: 55%
“…8B). Residues 526 to 528 are not exposed to extracellular MTSET upon depolarization, which is consistent with previous studies by Zhang et al (37), but are accessible to pCMBS (7,35). I521C was the residue with gating most dramatically affected by MTSET (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This analysis is supported by the modeling of Lee et al (10). An alternative view is that Shaker R1 aligns with hERG K1, and this is supported by S4 mutational studies (17) and the accessibility of the outer S4 region to pCMBS with depolarization (7). The outer four S4 positive charges in Shaker carry most of the activation gating charge (1,3,25), and mutation of the outer three charges in hERG to cysteines affects gating charge transfer the most (37).…”
mentioning
confidence: 94%
“…Effects of RTC-1 on the hERG channel currents were determined by the two-electrode voltage clamp technique as described previously (Elliott et al 2009 2) using microelectrodes made from borosilicate glass, filled with 3 M KCl, which had resistances between 0.5 and 2.0 M. The effects of compounds on tail currents at −50 mV were examined using a repeated pulse protocol. For this, control currents were first measured in Ringer's solution during repeated depolarizing steps (+ 30 mV) delivered from a holding potential of −80 mV.…”
Section: Effects Of Rtc-1 On the Herg Channelmentioning
confidence: 99%